Smart membrane materials and systems from flat membranes to microcapsule membranes - Chu, Liang-Yin (Advanced topics in science and technology in China., 2011)
Smart Membrane Materials and Systems: From Flat Membranes to Microcapsule Membranes comprehensively and systematically treats modern understanding of smart or intelligent membranes with environmental stimuli-responsive functions. The contents range from flat membranes to microcapsule membranes with various response properties, such as thermo-response, pH-response, glucose-response, molecular-recognition, and dual-/multi-stimuli-response. While chapters may be read as stand-alone, together they clearly describe cover design concepts, fabrication strategies and methods, microstructures and performances of smart membranes. Vivid schematics and illustrations throughout the book enhance accessibility to the theory and technologies. The book is intended for researchers and postgraduate students in membrane science and technology, separations and controlled-release.  Dr. Liang-Yin Chu is a professor at the School of Chemical Engineering, Sichuan University, China. He is a Distinguished Young Scholar of the National Natural Science Foundation of China and a Distinguished Professor of Chang Jiang Scholars Program of the Ministry of Education of China.